PHYSICAL EDUCATION IN SCHOOLS OF BOA VISTA-RR: CONTENTS AND THEMES ADOPTED BY THEIR SOCIAL ACTORS (Fiep Bulletin - online, 2010)
The objective of the study was identifying the contents and themes developed by physical education of teacher (PET) in elementary schools in the county of Boa Vista, Roraima, Brazil. An analysis of the composition of the classes and objectives designed by docents sustained the base for the study. 23 (twenty-three) schools participated in the study, in these, 30 (thirty) docents, of both sexes aged from 20 to 50 years (X=30,03±8,57 years), all volunteers. Their classes were observed by researchers, where by his own, a scouth, evaluated the dynamics of the procedures adopted by the teachers during the classes and the time wasted on them. An individual interview with closed questions and open answers was utilized to identify the aims of the classes administered. The data of the scouth and of the contents of the interview were treated by the analysis of the content, in the method of categorization (Bardin, 1977). The results found indicate a high variability regarding the time designated to classes of physical education in each school, the sport, in a restricted sense, is a theme recurrent to classes, besides all the complexity of the human movement and their relations with the other and with the society; in average more than 22 minutes are designed to free themes, where the docent doesn't exert any guidance and is allowed the participation of students. It is concluded that modifications are necessary in the conducts adopted by the PETs, in the approach of the content of teaching and in their methodology to guide better students to the practice of the human movement toward the formation of the citizen.
Keywords: school physical education; Contents of teaching; teaching planning